1) √x^{2}-4х+4 + √x^{2}-6х+9= 1 2)√11х+3-√2-х = √9х+7 -√х-2 3)√х-5 - √10-х = 3

hiraimomorin hiraimomorin    3   08.03.2019 06:45    2

Ответы
XOBasya XOBasya  07.06.2020 00:01

3)10-x=3    1) x^{2} -6x+9=1

-x=3-10          x^{2}-6x+9-1=0

-x=-7              x^{2}-2x-4x+9-1=0

x=7                 x^{2}-2x-4x+8=0  

                      x ×(x-2)-4x+8=0

                     x(x-2)-4(x-2)=0

                     (x-2)×(x-4)=0

                     x-2=0

                       x-4=0

                        x=2

                         x-4=0

                         x1=2

                         x2=4

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра